Village Owned Enterprise Survival Strategy by Raising Brand Awareness of Advertising Through Marketing on Social Media - deni danial kesa (Program Pendidikan Vokasi Universitas Indonesia, 2020)
Village, as the center of economic development, is always interesting to study, because the structure of thevillages in Indonesia generally supports the movement of the urban economy. The aim of this study was toanalyze the role of marketing and self-image in one of the village organs, namely the village-owned enterprises(BUMDES). One way of survival is how BUMDES can increase the brand awareness of the businesses andbusinesses it operates. Descriptive qualitative research is the method used. As one of the public services whoseobligation is to obtain additional revenue through the business sector, BUMDES conducts marketingcommunications to consumers and expands marketing networks by improving self-image through two strategies.Direct strategies or below the line, use indirect prepositions. Respondents' results show that there are steps thatneed to be taken to improve self-image, including trust, type of service and corporate accountability for a directstrategy, while the indirect strategy can be achieved through the creation of social network marketing usingsocial media, websites and other internet tools. Respondents' results show that there are steps that need to betaken to improve self-image, including trust, type of service and corporate accountability for a direct strategy,while the indirect strategy can be achieved through the creation of social network marketing using social media,websites and other internet tools. It is hoped that a good self-image will help to strengthen the BUMDESbusiness cycle and support village programs as the center of the nation's economic progress.Keywords: Self image, advertising, Marketing Strategy, Social media